Pulsating variable stars as tracers of galactic structure and interaction mechanisms - Moretti, Maria Ida <1982> (Alma Mater Studiorum - Università di Bologna, 2012)
My PhD project has been focused on the study of the pulsating variable stars in two ultra-faint dwarf spheroidal satellites of the Milky Way, namely, Leo IV and Hercules; and in two ﬁelds of the Large Magellanic Cloud (namely, the Gaia South Ecliptic Pole calibration ﬁeld, and the 30 Doradus region) that were repeatedly observed in the KS band by the VISTA Magellanic Cloud (VMC, PI M.R. Cioni) survey of the Magellanic System.